Tar Removal From Producer Gas Via Thermal And Catalytic Means In A Microwave Reactor - Anis, Samsudin (2014)
Tar in biomass producer gas should be removed to avoid blocking of the pipe lines and to allow producer gas utilization in Internal Combustion (IC) engines and turbines for power generation. Among the available tar removal methods, thermal and catalytic (thermocatalytic) treatments of tar are more attractive with improvement of the producer gas energy content by converting tar into combustible gases. However, the commonly applied thermocatalytic treatments are costly by the use of conventional heating mechanism that consumes high electrical energy. The alternative method of microwave heating is cost effective, simple and potential for process scale up. A modified commercial microwave oven was developed and characterized for thermocatalytic treatment of tar. Tar removal was conducted initially using tar model compounds (toluene and naphthalene) followed by real tar from producer gas derived from biomass gasification. Two treatments were conducted: thermal and catalytic treatments. Tar species and gases were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) and Gas Chromatography-Thermal Conductivity Detector (GC-TCD), respectively. Whilst, coke/soot deposited on the catalysts was determined using Thermogravimetric Analyzer (TGA).